PERBANDINGAN PREMEDIKASI FENTANIL 1 mcg/kgBB IV DAN 2 mcg/kgBB IV TERHADAP TEKANAN DARAH DAN NADI AKIBAT INTUBASI JALAN NAFAS PADA PASIEN YANG MENJALANI PEMBEDAHAN ELEKTIF DI RSUP Prof. Dr. R. D. KANDOU MANADO PERIODE NOVEMBER – DESEMBER 2014 - Berhimpong, Marsela J. A.; Tambajong, Harold; Lalenoh, Diana Ch. (e-CliniC, 2015)
Abstract: Intubation is a patent measure of securing and maintaining the airway. Fentanyl is a synthetic opioid that effectively blunts the sympathetic response to intubation and surgical stimulus. Fentanyl is often the primary choice of premedication and induction agent in general anesthesia due to its little depressant effect on cardiovascular system. Objective: To analyze the differences in blood pressure and pulse rate during intubation after administration of premedication fentanyl 1 mcg / kg iv premedication compared to fentanyl 2 mcg / kg iv. Methods: This is a prospective analytical study. The samples are 28 patients who were undergoing elective surgeries and were selected using purposive sampling method. The statistical test used is the average non-parametric test. Result: There is a change in blood pressure and pulse rate in patients who were given premedication fentanyl 1 mcg / kg iv and 2 mcg / kg iv (p <0.05). The use of fentanyl 1 mcg / kg iv and 2 mcg / kg iv showed no significant difference (p> 0.05), since both fentanyl 1 mcg / kg iv and 2 mcg / kg iv can lower both blood pressure and pulse rate. Conclusion: There is a change in blood pressure and pulse rate as a result of airway intubation in elective surgery patients who were given fentanyl 1mcg / kg iv and fentanyl 2 mcg / kg iv as premedications (p <0.05).Keywords: intubation, fentanyl, blood pressure, pulse rateAbstrak: Intubasi merupakan tindakan pengaman dan pemeliharaan jalan nafas paling paten. Fentanil adalah opioid sintesis yang efektif menumpulkan respon simpatis pada intubasi serta stimulus pembedahan. Fentanil seringkali menjadi pilihan utama agen premedikasi dan induksi dalam anestesia umum karena sedikit mendepresi kardiovaskular. Tujuan: Untuk menganalisis perbedaan tekanan darah dan laju nadi pada tindakan intubasi setelah pemberian premedikasi fentanil 1 mcg/kgbb iv dibandingkan dengan premedikasi fentanil 2 mcg/kgbb iv. Metode penelitian: Penelitian ini merupakan penelitian analisis prospektif. Sampel ialah 28 pasien yang menjalani bedah elektif. Cara pengambilan sampel dilakukan dengan metode purposive sampling. Uji statistik menggunakan uji rerata non parametrik. Hasil penelitian: terdapat perubahan tekanan darah dan nadi pada pasien yang diberikan premedikasi fentanil 1 mcg/kgbb iv dan 2 mcg/kgbb iv (p < 0,05). Penggunaan fentanil 1 mcg/kgbb iv dan 2 mcg/kgbb iv menunjukkan tidak terdapat perbedaan yang signifikan (p>0,05), baik fentanil 1 mcg/kgbb iv dan 2 mcg/kgbb iv keduanya dapat menurunkan tekanan darah dan laju nadi. Simpulan: Terdapat perubahan tekanan darah dan laju nadi akibat intubasi jalan nafas pada pasien pembedahan elektif yang diberikan premedikasi fentanil 1mcg/kgbb iv dan fentanil 2 mcg/kgbb iv (p < 0,05).Kata kunci: intubasi, fentanil, tekanan darah, laju nadi